2021
DOI: 10.1080/14686996.2021.1920821
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance in polymorphic heavily Co-doped Cu2SnS3 through carrier compensation by Sb substitution

Abstract: 2021): Enhanced thermoelectric performance in polymorphic heavily Co-doped Cu 2 SnS 3 through carrier compensation by Sb substitution, Science and Technology of Advanced Materials,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…For samples TS2 (S ~250-400 µV/K, ρ ~1.5-1.1 mΩ-m) and TS3 (S ~325-425 µV/K, ρ ~3.5-1.5 mΩ-m), the TE measurements were repeatable during the measurement cycles, and the values of S and ρ were in agreement with the literature [7,15]. Although we observed an increased amount of SnO 2 and the formation of a new SnO phase, segregation of SnS was not observed.…”
Section: Sample Name Atomic Fraction (±1%)supporting
confidence: 88%
See 1 more Smart Citation
“…For samples TS2 (S ~250-400 µV/K, ρ ~1.5-1.1 mΩ-m) and TS3 (S ~325-425 µV/K, ρ ~3.5-1.5 mΩ-m), the TE measurements were repeatable during the measurement cycles, and the values of S and ρ were in agreement with the literature [7,15]. Although we observed an increased amount of SnO 2 and the formation of a new SnO phase, segregation of SnS was not observed.…”
Section: Sample Name Atomic Fraction (±1%)supporting
confidence: 88%
“…In this temperature range, sulphides of copper and tin or copper and iron can be viable alternatives. Gu et al [14] discussed 3D modulation doping of CuCo 2 S 4 in CTS and reported a zT ~0.82 at 773 K. Zhao et al [15] reported simultaneous Co and Sb substitution in the CTS system resulting in a zT of ~0.88 at 773 K. Furthermore, Deng et al [16] reported a zT of ~1 in a similar Cu 7 Sn 3 S 10 system through Br-doping. A zT of ~0.4-0.8 above 700 K is regularly reported for CTS by In [17], Zn [7], Mn [18], Ni [19], Fe [20], Co [21], and Cu [22] substitution at the Sn site, aiming to enhance the carrier concentration and reduce the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of decreasing the hole concentration while retaining the semiordering character of this phase beneficial for suppressing heat transport, we have investigated the aliovalent substitution of Sb 5+ for Sn 4+ , as reported recently in Cu 2 SnS 3 and Cu 3 SnS 4 . 8,57,58 We have fixed the pristine composition to that determined from synchrotron XRD data, i.e., Cu 22 Sn 10 S 32 corresponding to x = 0.063 in the Cu 2+x Sn 1−x S 3 series. For comparison purposes, we also include the thermoelectric properties of the x = 0.075 sample.…”
Section: Resultsmentioning
confidence: 99%
“…With the aim to decrease the hole concentration while retaining the semi-ordering character of this phase beneficial for suppressing the heat transport, we have investigated the aliovalent substitution of Sb 5+ for Sn 4+ , as reported recently in Cu2SnS3 and Cu3SnS4. 8,57,58 We have fixed the pristine composition to the one determined from synchrotron X-ray diffraction data, i. Cu26V2Ge6-xSbxS32. 56 As anticipated, the substitution of Sb for Sn in Cu22Sn10S32 results in a significant decrease in the hole concentration, reflected by the simultaneous increase in r and S.…”
Section: Cu22sn10-ysbys32 Seriesmentioning
confidence: 99%
“…CTS is a direct-gap semiconductor containing 3 bands derived from strongly hybridized Cu-3d and S-3p orbitals in the valence band edge and one single band from Sn-4s in the conduction band edge, which ensures a superior P-type TE performance as compared to N-types with a 3-dimensional Cu–S and S–S network as the transport channel for holes. 11,12 It has a very low κ l at high temperatures, particularly in the highly cation-disordered cubic and tetragonal phases, that is similar to its theoretical minimum of 0.3 W m −1 K −1 at 773 K. 7,13 By doping at the Sn site with transition metal atoms (Zn, 14 Ni, 15 Co, 7 Fe 16 ), CTS can be tuned to reach a wide carrier concentration, p , ranging from 10 19 to 10 21 cm −3 , with a large σ up to approximately 2000 S cm −1 (300 K), and a high PF up to 8–11 μW cm −1 K −2 at 723–773 K, despite the modest S . 7…”
Section: Introductionmentioning
confidence: 62%